Supercritical carbon dioxide extraction of constituents of pithecellobium jiringan seeds and their identification using time of flight gas spectrometry - C. Y., Mohd. Azizi; N. A., Nik Norulaini; Setianto, Wahyu; A. K., Mohd. Omar (2006)
Supercritical carbon dioxide was used as a solvent in the extraction of p. Jiringan jack seeds. Fast gas chromatography/ time of flight mass spectrometry (tof-gcms) performed the identification and quantification of the oil extract compounds. The aims of this work were to study the effect of supercritical condition on the global extraction yield and compound characterization at difference pressure of 20.68 mpa and 48.26 mpa and constant temperature of 70 o c during 100-minute extraction time. The highest percentage yield of 4.5 % was obtained at 48.26 mpa. By assigned the percentage of matching as 80%, total of 44 compounds were identified at both pressure of 48.26 mpa and 20.68 mpa, meanwhile the composition of oil extract was changes with extraction pressure. The major compounds extracted at both operating pressure were an essential oil, fatty acid, fatty acid methyl ester, the ally sulfur and the hydrocarbon and derivatives. At 20.68 mpa, the composition of essential oil compounds contributed for almost 58% of the oil constituents. The increased of pressure will be effect the profiling of the compounds. Group of ally sulfur could be extract only at 20.68 mpa, meanwhile the composition of squalene decrease with increasing of pressure. The compounds of long chain hydrocarbon and long chain fatty acids were present at 48.26 mpa but none at 20.68 mpa.